Effect of ultrasound irradiation on asphaltene aggregation and implications to rheological behavior of bitumen - Nguele, Ronald; Okawa, Hirokazu (Ultrasonics sonochemistry, 2021)
•The contribution of asphaltene aggregation to bitumen viscosity is studied.•The ultrasound waves reduce the viscosity of the bitumen.•The applied frequency and the gas environment influence the bitumen viscosity reduction.•A positive correlation between the asphaltene yield and the viscosity is established. The present work investigates the contribution of asphaltene aggregation to bitumen viscosity subject to ultrasound irradiation. A West-African bitumen with a viscosity of 12043cP at room temperature was sonicated at low (38 kHz) and mild frequency (200 kHz) under controlled gas environment including air, nitrogen (N2) and carbon dioxide (CO2). The rheology of the bitumen, asphaltene content analyses as well as spectral studies were conducted. Herein was found that sonicating the bitumen at 200 kHz under air-environment reduces the initial viscosity up to 2079cP, which was twice larger than that obtained when a low frequency was used. In respect of the gas environment, it was shown that ultrasound irradiation under N2 environment could lower the bitumen viscosity up to 3274cP. A positive correlation between the asphaltene content and the viscosity reduction was established. The results from the spectral analyses including Fast Fourier Infrared and the observations from Scanned Electron Microscope were consistent with the rheological studies and led to the argument that the viscosity reduction results from either the scission of long chain molecules attached to the aromatic rings (when the applied frequency was altered under fixed gas environment) or the self-aggregation of asphaltene monomers (when gas environment was changed at fixed frequency).